UPAYA PENCEGAHAN VIRUS COVID-19 MELALUI PEMANFAATAN TEKNOLOGI DI KELURAHAN PAJANG KOTA TANGERANG - Woelandari Fathonah (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
Based on the records of the COVID-19 handling task force on July 1, 2021, the city of Tangerang is included in the COVID-19 red zone. Pajang Village is one of the villages in the Tangerang city area. This community service activity is carried out as an effort to prevent the spread of the COVID-19 virus in Pajang Village through the use of technology. This community service activity aims to minimize the spread of the COVID-19 virus through the distribution of posters and videos to local residents. This activity was carried out in stages consisting of preparation, making posters and videos about COVID-19, distributing posters and videos virtually and evaluating activities. For making posters, the process of collecting information related to the posters to be made is carried out. On the poster, points related to the poster's theme are presented. Similar to posters, making a video is done by studying literature first and then applying it in the form of a video. The videos made can convey brief information in informative language. The distribution of posters and videos is done through social media such as whatsapp, youtube and instagram. Through this activity, posters and videos have been successfully distributed through social media such as Instagram which is integrated with the Benda sub-district Instagram, YouTube and Whatsapp. Efforts to handle the spread of COVID-19 through the use of technology are quite effective during PPKM. The results of this activity received a fairly good response from the kelurahan and the local community and it is hoped that in the face of this COVID-19 pandemic, the local community will continue to carry out health protocols wherever they are and it is necessary to carry out further incentive activities in an effort to prevent the spread of COVID-19.